2021
DOI: 10.14245/ns.2142248.124
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Transforaminal Lumbar Interbody Fusion Using Unilateral Versus Bilateral Interbody Cages

Abstract: Objective: To assess the impact of bilateral versus unilateral interbody cages on outcomes for minimally invasive transforaminal lumbar interbody fusion (MIS TLIF) procedures.Methods: A retrospective review for primary, elective, single-level MIS TLIF procedures with bilateral posterior instrumentation from 2008–2020 was performed. Patients were grouped according to unilateral or bilateral interbody cage use. Procedures performed without static interbody cages or indicated for trauma, infection, malignancy wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…VAS-Leg pain score was evaluated in 8 studies including 518 patients ( 20 , 21 , 23 , 25 , 27 , 29 , 31 , 32 ). The results of the fixed-effect model meta-analysis showed that: the overall difference between UPSF and BPSF was not statistically significant [SMD = 0.18, 95% CI (−0.00–0.36), P = 0.05; Figure 3 ].…”
Section: Resultsmentioning
confidence: 99%
“…VAS-Leg pain score was evaluated in 8 studies including 518 patients ( 20 , 21 , 23 , 25 , 27 , 29 , 31 , 32 ). The results of the fixed-effect model meta-analysis showed that: the overall difference between UPSF and BPSF was not statistically significant [SMD = 0.18, 95% CI (−0.00–0.36), P = 0.05; Figure 3 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our case series demonstrated an average procedure time of 160.6 ± 31.9 minutes, suggesting that our AR-integrated workflow does not cause a relevant delay of the procedure. 4,25 However, our current study model does not allow us to determine the impact the use of AR has on duration of MIS-TLIF. The purpose of the current study was to develop an effective protocol for the reproducible application of AR for the MIS-TLIF.…”
Section: Discussionmentioning
confidence: 99%
“…The overall procedure time of a tubular MIS-TLIF in the literature is reported between 138.3±33.3 and 210.6±11.93 minutes. Our case series demonstrated an average procedure time of 160.6±31.9 minutes, suggesting that our AR-integrated workflow does not cause a relevant delay of the procedure [ 4 , 25 ]. However, our current study model does not allow us to determine the impact the use of AR has on duration of MIS-TLIF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations